A review on the physico-chemical properties of solvent influencing the solubility of drugs - Vamshi Krishna Tippavajhala (Journal of Global Pharma Technology, 2017)
As the bioavailability of drugs from liquid orals mainly depends on their solubility in the given solvent system, it is considered as one of the important parameters for assessing the absorption of drugs into the systemic circulation. Because of this, lot of emphasis has been given to the various factors affecting the solubility of drugs. One among these factors is the physico-chemical properties of the solvent. In this context, the present review article details various physico-chemical properties of the solvent that can influence the solubility of drugs and thereby affecting their bioavailability. Study of these factors helps a researcher in the selection of a solvent system with an optimal solubility of the drug that can lead to an improved bioavailability.Keywords: Solubility, Physico-chemical properties of solvent.